Effect of processing on antioxidant potential and total phenolics content in beet (Beta vulgaris L.) - Raupp, Dorivaldo da Silva; Rodrigues, Eliseu; Rockenbach, Ismael Ivan; Carbonar, Aline; Campos, Priscilla Faber de; Borsato, Aurélio Vinicius; Fett, Roseane (My University, 2011)
The antioxidant capacity of beet is associated with non-nutritive constituents, such as phenolic compounds. The purpose of this research was to evaluate the effect of two different heat-processing techniques (drying and canned) on the antioxidant potential (ABTS) and phenolics content of beets. A forced air circulation dehydrator was used for the drying. Drying at high temperatures (100 + 90 °C/5.6 hours; 90 °C/6 hours) increased the antioxidant potential of the processed products while mild drying conditions decreased it (80 °C/6 hours; 100 + 70 °C/6 hours) or had no effect on it (70 °C/7 hours; 100 + 80 °C/6 hours). For the canned products, the antioxidant potential did not differ according to the pH (4.2 to 3.8) for any of the four acids tested. Some processing methods influenced the antioxidant potential of the processed products, and this was also dependent on changes in the total phenolics content.

O potencial antioxidante da beterraba está associado com seus constituintes não nutritivos, como os compostos fenólicos. A proposta da pesquisa foi avaliar o efeito de duas diferentes técnicas de processos (secagem e processamento de conservas) sobre o potencial antioxidante (ABTS) e o conteúdo de fenólicos de beterraba. Foi usado um secador de circulação forçada de ar para a secagem. Secagem em altas temperaturas (100 + 90 °C/5,6 horas; 90 °C/6 horas) aumentaram o potencial antioxidante dos produtos processados, enquanto que condições brandas, comparativamente, diminuíram (80 °C/6 horas; 100 + 70 °C/6 horas) ou não tiveram efeito (70 °C/7 horas; 100 + 80 °C/6 horas). Nos processos de conservas, o potencial antioxidante não diferiu com a variação de pH (4,2 to 3,8), para qualquer dos quatro ingredientes acídicos testados. Alguns métodos de processamento interferiram no potencial antioxidante dos produtos obtidos, e isso dependeu também de mudanças no conteúdo fenólico total.
Efeito do processamento no potencial antioxidante e conteúdo de fenólicos totais de beterraba (Beta vulgaris L.)
Keywords: Beta vulgaris; Beet; Antioxidant activity; Phenolic compounds